Impact of inflammatory bowel disease on partners: a qualitative study. (2nd April 2022) - Thapwong, Parichat; Norton, Christine; Terry, Helen; Czuber-Dochan, Wladyslawa
Abstract : Background: Extensive studies have documented the impacts of inflammatory bowel disease (IBD) on patient quality of life, but this study addresses the gap concerning IBD outcomes for the family members of adult IBD patients. Aims: To explore the lived experience of IBD patients and their family members regarding impacts of IBD on family members and their coping strategies. Methods: Semi-structured, in-depth, online interviews were held via Skype, Microsoft Teams and Zoom from February to June 2020, with 12 purposively selected participants, comprising six IBD patients with their six partners. Interviews were audio-recorded and transcribed verbatim, for inductive thematic data analysis. Results: Four main themes emerged during the analysis under the central theme 'our relationship with IBD, for better or worse'. The theme 'our relationship' revealed the impact of IBD on intimate relationships, family planning, role change as partner and carer, and the importance of honest communication. IBD also affected wider relationships with family, children and social life, but teamwork could mediate negative impacts on relationships. Living in constant fear and guilt impacted on emotional wellbeing. Humour and knowledge of IBD reduced negative impacts. IBD had impacts on everyday life (diet, finances and travel) for both patients and partners. Planning for uncertain situations was helpful to reduce restrictions. Conclusions: There are wide-ranging implications for healthcare providers (gastroenterologists, GPs and IBD nurses), social care professionals (psychologists and social workers), family therapists and researchers who could incorporate a bio-psycho-social approach to working with patients with IBD to improve services for individuals who have IBD and their partners and families.